Child participation and involvement in child protection committees in Mutare district; - Tapera, Tsitsi (Midlands State University, 2017)
The dissertation’s main aim is to look closely at Child Participation and Involvement in Child Protection Committees in Mutare District. Dora ward 5, Mutare rural was used as the case study in this study. The research objectives were to investigate the community’s understanding of child rights and child participation and verify the extent and levels of child participation and involvement as a right in Child Protection Committees within Dora ward 5, as well as to document and devise strategies for enhancing child participation in child protection activities. The researcher employed qualitative research methodologies. A total of 6 key informants’ interviews were conducted and 2 focus group discussions were held with community child protection committee members and children separately. Findings from the research indicated that child participation is still limited in development initiatives and Child Protection Committees in the ward. There is still emphasis on protective and provision rights neglecting child participation rights. Children are still limited to participation in their own child led Child Protection Committee. The study recommends the scaling up of advocacy for the proper mainstreaming of child participation in Child Protection Committees